Diarrheal microbiota-derived extracellular vesicles drive intestinal homeostasis dysfunction via miR-125b/NF-κB-mediated macrophage polarization - Mengzhen Song; Wenjun Zhou; Jinping Fan; Chenhao Jia; Wen Xiong; Hong Wei; Shiyu Tao (Gut Microbes)
Gut microbiota-derived extracellular vesicles (EVs) are emerging mediators of microbiota-host crosstalk, but their roles in diarrheal diseases remain poorly understood. Here, we revealed that EVs isolated from diarrheal donors’ intestinal microbiota trigger pro-inflammatory macrophage polarization and compromise intestinal epithelial barrier integrity in both conventional and pseudo-germ-free mice, demonstrating their intrinsic pathogenicity independent of viable microbes. miRNAs sequencing analysis identified miR-125b as a highly enriched miRNA in diarrheal microbiota-derived EVs, which directly targets the 3’ untranslated region of NF-κBIA, leading to its degradation and subsequent activation of the NF-κB signaling pathway. This molecular cascade drives macrophages toward a pro-inflammatory phenotype characterized by elevated TNF-α and IL-1β secretion, ultimately disrupting tight junction proteins (ZO-1, Occludin) and increasing intestinal permeability. Strikingly, adoptive transfer of primary macrophages pre-exposed to miR-125b recapitulated barrier dysfunction in recipient mice. Our study uncovers a tripartite axis linking diarrheal microbiota-derived EVs, pro-inflammatory macrophage polarization via EVs-miR-125b, and intestinal homeostasis breakdown, highlighting the underappreciated role of EVs-borne miRNAs in reshaping host immunity. These findings position EVs as both biomarkers and potential targets for further exploration for diarrhea-related inflammatory gut disorders, offering a nanotechnology-inspired strategy to modulate EVs-mediated interkingdom communication in microbiome-associated diseases.